Jieduquyuziyin Prescription Suppresses Inflammatory Activity of MRL/lpr Mice and Their Bone Marrow-Derived Macrophages via Inhibiting Expression of IRAK1-NF-κB Signaling Pathway - Ji, Lina; Fan, Xuemin; Hou, Xiaoli; Fu, Danqing; Bao, Jie; Zhuang, Aiwen; Chen, Sixiang; Fan, Yongsheng; Li, Rongqun (Frontiers in Pharmacology, 2020)
Jieduquyuziyin prescription (JP) has been used to treat systemic lupus erythematosus (SLE). Although the effectiveness of JP in the treatment of SLE has been clinically proven, the underlying mechanisms have yet to be completely understood. We observed the therapeutic actions of JP in MRL/lpr mice and their bone marrow-derived macrophages (BMDMs) and the potential mechanism of their inhibition of inflammatory activity. To estimate the effect of JP on suppressing inflammatory activity, BMDMs of MRL/lpr and MRL/MP mice were treated with JP-treated serum, and MRL/lpr mice were treated by JP for eight weeks. Among them, JP and its treated serum were subjected to quality control, and BMDMs were separated and identified. The results showed that in the JP group of BMDMs stimulated by Lipopolysaccharide (LPS) in MRL/lpr mice, the secretion of interleukin-6 (IL-6) and tumor necrosis factor- (TNF-) was reduced, and the expressions of Interleukin-1 receptor-associated kinase 1 (IRAK1) and its downstream nuclear factor B (NF-B) pathway were decreased. Meanwhile, the alleviation of renal pathological damage, the decrease of urinary protein and serum anti-dsDNA contents, the inhibition of TNF- level and then the suppression of the IRAK1-NF-B inflammatory signaling in the spleen and kidney, confirmed that the therapeutic effect of JP. These results demonstrated that JP could inhibit the inflammatory activity of MRL/lpr mice and their BMDMs by suppressing the activation of IRAK1-NF-B signaling and was supposed to be a good choice for the treatment of SLE.